2009
DOI: 10.26719/2009.15.3.717
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO and Rh D blood groups in the population of Poonch district, Azad Jammu and Kashmir

Abstract: We evaluated the distribution of ABO and Rhesus (Rh) D blood groups in the population of Poonch district in Azad Jammu and Kashmir. The blood group phenotypes were detected by the classic slide method. The ABO blood group system in the total sample showed the same trend of prevalence as for the general Indian subcontinent (B ≥ O > A > AB). The same trend was found among males, but among females the order of prevalence was different (O B > A > AB). However, the allelic frequencies in both sexes were in the orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
4
14
1
Order By: Relevance
“…Among other centres in Northern India and neighbouring country Pakistan, the trend of ABO frequency was same as B>O>A>AB blood groups but the frequency of A blood group among Kumaon population in Uttarakhand (28.7%) and neighbouring Nepal(34%) was reported to be higher as compared to other parts of North. [6][7][8][9][10][11] Similar observations of 'B' blood group being the commonest were made from Western states. 12,13 The distribution of ABO and RhD blood groups when compared to the studies done at eastern or southern parts of the country and few other parts of the world showed contrasting observations wherein blood group O is the most prevalent.…”
Section: Discussionsupporting
confidence: 54%
“…Among other centres in Northern India and neighbouring country Pakistan, the trend of ABO frequency was same as B>O>A>AB blood groups but the frequency of A blood group among Kumaon population in Uttarakhand (28.7%) and neighbouring Nepal(34%) was reported to be higher as compared to other parts of North. [6][7][8][9][10][11] Similar observations of 'B' blood group being the commonest were made from Western states. 12,13 The distribution of ABO and RhD blood groups when compared to the studies done at eastern or southern parts of the country and few other parts of the world showed contrasting observations wherein blood group O is the most prevalent.…”
Section: Discussionsupporting
confidence: 54%
“…Studies done in India, Pakistan and Bangladesh have found similar trends in distribution of ABO blood groups with higher frequencies of blood group B. [11][12][13][14][15][16][17] A study in Zammu and Kashmir reported blood group B as the commonest one (36.6%) followed by groups O (35%), A (21.4%) and AB (7%). 11 In another study in Kashmir, blood group O was reported as the most common one (38.43%), followed by groups B (32.05%), A (22.95%) and AB (6.55%).…”
Section: Resultsmentioning
confidence: 98%
“…[11][12][13][14][15][16][17] A study in Zammu and Kashmir reported blood group B as the commonest one (36.6%) followed by groups O (35%), A (21.4%) and AB (7%). 11 In another study in Kashmir, blood group O was reported as the most common one (38.43%), followed by groups B (32.05%), A (22.95%) and AB (6.55%). 12 In Vellore, blood group O was the most common (38.75%) followed by B (32.69%), A (18.85%) and AB (5.27%).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the studies conducted on Nepalese medical students by Pramanik and Pramanik [16] and on a report by Tomilin and Gurtovaia [20] on a population of the Russian Federation, A was the most prevalent blood group. Similarly [21], reported that blood group B was the most prevalent one in Bannu region in Pakistan. Such contradictions are probably due to immensely different sample sizes, geographical environments and ethnic groups in the study populations.…”
Section: Discussionmentioning
confidence: 95%